2004
DOI: 10.3136/fstr.10.341
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Light-Induced Glycoalkaloids, .ALPHA.-Solanine and .ALPHA.-Chaconine, in Four Potato Cultivars (Solanum tuberosum L.) Distributed in Japan by LC/MS

Abstract: The major glycoalkaloids, a-solanine and a-chaconine, in potato tubers were determined by LC/ESI-MS. The average recoveries from spiked samples by the method used in this study were more than 94% with RSD of analytical values less than 5% for both oe-solanine and a-chaconine. The total glycoalkaloid contents in tubers of four potato cultivars distributed in Japan, cv. Irish Cobbler, Touya, May Queen, and Sayaka, were compared. There was no significant difference in glycoalkaloid content between immature and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
0
4
1
Order By: Relevance
“…Likewise, potato tuber extracts were expected to show anti‐inflammatory activity in macrophage cells due to their high content of glycoalkaloids such as α‐solanine, as previously shown (Kenny et al, 2013; Shin et al, 2016). However, this did not hold true in the current study (Figure 2), possibly because the glycoalkaloid content in tubers of Sayaka, the potato cultivar used in this study, is lower than that in other cultivars, as shown in May Queen (Chuda et al, 2004). More intriguingly, although extracts from transgenic potato tubers with enriched betacyanins contain substantial amounts of betanin (239 µM) and isobetanin (20 µM) in the original tuber extract of Pb1 [estimated from Figure 1a]), the extracts at 100~10000 fold dilutions failed to exhibit significant anti‐inflammatory activity (Figure 2).…”
Section: Discussioncontrasting
confidence: 66%
“…Likewise, potato tuber extracts were expected to show anti‐inflammatory activity in macrophage cells due to their high content of glycoalkaloids such as α‐solanine, as previously shown (Kenny et al, 2013; Shin et al, 2016). However, this did not hold true in the current study (Figure 2), possibly because the glycoalkaloid content in tubers of Sayaka, the potato cultivar used in this study, is lower than that in other cultivars, as shown in May Queen (Chuda et al, 2004). More intriguingly, although extracts from transgenic potato tubers with enriched betacyanins contain substantial amounts of betanin (239 µM) and isobetanin (20 µM) in the original tuber extract of Pb1 [estimated from Figure 1a]), the extracts at 100~10000 fold dilutions failed to exhibit significant anti‐inflammatory activity (Figure 2).…”
Section: Discussioncontrasting
confidence: 66%
“…Glycoalkaloid levels in potatoes traded in the market may be influenced by transportation and storage conditions (Chuda et al, 2004). Potatoes that are sprouting or subjected to light exposure, inappropriate storage, extreme temperature, wounding, and mechanical injury accumulate glycoalkaloids at a faster rate (Cantwell, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…[1] However, toxic steroidal glycoalkaloids are ubiquitous in potato products because these biotoxins play key roles in natural plant protection from mould and insect infestation. [2] The two major toxins, α-solanine and α-chaconine, usually comprise more than 95% of the total steroidal glycoalkaloid content in potatoes. Although these toxins are present in all parts of the potato plant, the skins and the sprouts contain the highest concentration of glycoalkaloids.…”
Section: Introductionmentioning
confidence: 99%
“…[1] These compounds play an important role in natural plant protection, [3] and it has also been established that stresses such as exposure to light, frost damage and tissue wounding during harvesting can lead to an accumulation of these toxic glycoalkaloids in potatoes. [2,4,5] Glycoalkaloid content of ca 15 mg/kg can result in a bitter taste in potatoes while levels at or greater than 200 mg/kg are considered hazardous to human health. [5 -7] Lachman et al reported that higher levels of α-solanine can cause a burning sensation in the throat and mouth.…”
Section: Introductionmentioning
confidence: 99%